Assessing Need for Training Postgraduate on Social Security in Vietnam - Hai Trung Nguyễn (Asian Social Work Journal, 2018)
This paper aims to assess the Need for Training Postgraduate on Social Security in Vietnam. Base on questionnaires from 400 to staff working in the field of social security and deep interviews of 30 people which are experts, lecturers in university, the result of this study has described a general picture about need of social security training. Specifically, findings show that: for the Strengths and Opportunities: First, the State always has the right policies on social security. Ensuring social security for every people is the consistent policy in Vietnam; Second, the social security units are increasingly being developed in terms of quantity and quality; Third, human resources in this area are enthusiastic, experience and qualified but just some of them have degree related to social security; Fourth, there has been a great deal of interest from the State for improving the quality of human resources in supplementing their knowledge of Social Security through National programs and projects; Fifth, educational institutions have been paying more attention, spending more time and funds for the training and developing capacity of lecturers in social security; Sixth, numbers of educational institutions having social security subjects in their training curriculum have increased faster. Weakness and Threats: First, despite the attention of the Party and the State, Vietnam social security policy system is scattered, overlapped; Second, number of staff working in the social security sector is largely unskilled and unqualified in term of social security knowledge; Third, for educational institutions: there has been interest and investment in research, teaching and training in the social security industry but still limited; lecturers with a degree in Social Security are also very limited. Most of them switched from other specialization; most of the educational institutions do not have clear orientation to develop Social Security curriculum at postgraduate level; the syllabus for social security topics is not much. Many new curriculums are translated from foreign materials so some contents are not completely suitable with the situation of Vietnam; currently, there is no social security training code. Base on the SOWT, this paper has discussed and recommended solutions to develop social security training program at postgraduate level to meet the need of high quality human resources on social security in Vietnam.